Homo Economicus - Herry Priyono, B. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
Human being is driven by many factors, but in trading activities, an individual is driven primarily by self-interest rather than other encouragement. This is the point which then develops into the core of the image of an economic being. However, the whole of human self is never driven only by self-interest. Through the history of the idea of homo economicus, what was originally a particular point of view about humans turned into a claim about the whole of human nature. The actions and behaviours of homo economicus were still driven by self-interest, but what was meant by self-interest was no longer in its classical sense. Its meaning has been much more extensive. This article shows the ambiguity of the idea of homo economicus: what was originally a certain point of view about human being, was applied to human nature and then became an agenda of how human beings and society should be. Humans must be homo economicus, but the latter is definitely not the whole picture of human nature. The image of an economic being is not the real description of the nature of human self, for it has its own territory. It is not the economic beings that gave birth to economics, but the economics that created economic beings.